Pengaruh Ukuran Perusahaan, Leverage, Likuiditas Terhadap Kualitas Laba Dengan Kepemilikan Institusional Sebagai Moderasi (Studi Empiris Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di Bei Tahun 2021-2023) - Kharisma Putri Ramadhani; Andy Dwi Bayu Bawono (Jurnal Economic Resource, 2026)
This study seeks to examine the impact of firm size, leverage, and liquidity on earnings quality, with institutional ownership serving as a moderating variable, in food and beverage companies listed on the Indonesia Stock Exchange from 2021 to 2023. The quality of earnings is increasingly significant due to the rising operational complexity of companies and the ongoing occurrence of financial statement restatements. This study employs a quantitative methodology utilising secondary data derived from corporate financial statements and annual reports. The research sample comprised 138 observations analysed through multiple linear regression utilising IBM SPSS software. The research findings demonstrate that leverage exerts a positive and significant partial influence on earnings quality, whereas liquidity has a negative and significant impact on earnings quality. Simultaneously, firm size exerts no substantial influence on earnings quality. Moderation testing indicates that institutional ownership can moderate the relationship between firm size and earnings quality, but it does not moderate the relationship between leverage and liquidity and earnings quality. All independent and interaction variables were simultaneously demonstrated to significantly influence earnings quality. The findings suggest that the contractual obligations of debt and short-term financial conditions significantly influence earnings quality, whereas company size necessitates robust oversight mechanisms to yield a beneficial effect. This research theoretically reinforces agency theory and signalling theory, while practically offering implications for management, investors, and regulators to enhance the quality of financial reporting.